Reducing mortality from 2019-nCoV: host-directed therapies should be an option - Zumla, Alimuddin; Hui, David S; Azhar, Esam I; Memish, Ziad A; Maeurer, Markus (The Lancet (British edition), 2020)
All three coronaviruses induce excessive and aberrant non-effective host immune responses that are associated with severe lung pathology, leading to death.2–4 Similar to patients with SARS-CoV and MERS-CoV, some patients with 2019-nCoV develop acute respiratory distress syndrome (ARDS) with characteristic pulmonary ground glass changes on imaging. In most moribund patients, 2019-nCoV infection is also associated with a cytokine storm, which is characterised by increased plasma concentrations of interleukins 2, 7, and 10, granulocyte-colony stimulating factor, interferon-γ-inducible protein 10, monocyte chemoattractant protein 1, macrophage inflammatory protein 1 alpha, and tumour necrosis factor α.2–6 In those who survive intensive care, these aberrant and excessive immune responses lead to long-term lung damage and fibrosis, causing functional disability and reduced quality of life.7,8 Specific drugs to treat 2019-nCoV will take several years to develop and evaluate. Infection with 2019-nCoV appears to be initially associated with an increased Th2 response,4 which might reflect a physiological reaction to curb overt inflammatory responses, a clinical phenomenon that guided the optimal timing of interferon treatment in patients with sepsis, resulting in increased survival.14 Interleukin 17 blockade might benefit those patients who have a 2019-nCoV infection and increased plasma concentration of interleukin 17.